Add the polynomials (9x - 6) + (- 5x + 7)

Mathematics
Tutor: None Selected Time limit: 1 Day

just doing homework

Nov 25th, 2014

(9x - 6) + (- 5x + 7)

Now we open the brackets, then we get

= 9x - 6 - 5x + 7

Now separate the like terms, we get

= 9x - 5x + 7 - 6

= x(9 - 5) + 1

= x(4) + 1

= 4x + 1

Hence     (9x - 6) + (- 5x + 7) = 4x + 1

Nov 25th, 2014

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Nov 25th, 2014
...
Nov 25th, 2014
Feb 26th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer